Synthesis, characterization, spectroscopic and theoretical studies of transition metal complexes of new nano Schiff base derived from l‐histidine and 2‐acetylferrocene and evaluation of biological and anticancer activities. (18th May 2018) - Mahmoud, Walaa H.; Omar, M.M.; Sayed, Fatma N.; Mohamed, Gehad G.
Abstract : A new Schiff base derived from the condensation of 2‐acetylferrocene withl ‐histidine was prepared and characterized using elemental analyses and spectroscopic methods. Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes of the Schiff base were prepared and characterized using various physicochemical methods such as elemental analysis, Fourier transform infrared and UV–visible spectroscopies, molar conductance, thermal analysis and scanning electron microscopy (SEM). Both ligand and complexes were investigated for their biological and anticancer activities. The elemental analyses showed that complexes were formed in a metal‐to‐ligand ratio of 1:1 stoichiometry. The spectral analyses proved that the ligand was tridentate and all complexes had an octahedral geometry, except the Zn(II) complex that was tetrahedral. SEM showed that the ligand and its Cd(II) complex were of nanometric structure. The molecular and electronic structure of the free ligand was optimized theoretically and the quantum chemical parameters were calculated. The molecular structure can be used to investigate the coordination sites and the total charge density around each atom. According to anticancer studies, Cd(II) complex was recommended to be used as anti‐breast cancer drug as it had very low IC50 (3.5 μg ml −1 ). Molecular docking was used to predict the binding between the free ligand and its Cd(II) complex and crystal structure of Staphylococcus aureus (PDB ID: 3Q8u), receptors of breast cancer mutant oxidoreductase (PDB ID: 3Hb5) and crystal structure of Escherichia coli (PDB ID: 3 T88) and to identify the binding mode and the crucial functional groups interacting with the three proteins. Abstract : Three‐dimensional plot of the interaction between Cd(II) complex and receptors of 3HB5.